Forty years later, a systematic literature review on inclusion in physical education (1975–2015): A teacher perspective. (November 2016) - Tant, Maxime; Watelain, Eric
Abstract: The first objective of this work is to systematically list the international studies about the inclusion of students with disabilities in physical education (PE) from the teachers' perspective. Sixty studies met our selection criteria and are listed. The second objective is to analyse the content of the literature according to the inductive and thematic approach of Thomas and Harden (2008). Our thematic analysis highlights: a) the factors that influence PE teachers' positive or negative attitudes and predispositions towards the inclusion of students with disabilities and b) the factors that can positively influence the inclusion of students with disabilities in PE classes, according to the teachers' representations. Based on these sets of factors, we propose some adapted PE training content for PE teachers. These training content proposals form the basis of research perspectives. Highlights: We review the inclusion of students with disabilities in physical education (PE) from the teachers' perspective. We highlight the factors that influence the PE teachers' attitudes towards the inclusion of students with disabilities. We highlight the factors that can positively influence the inclusion, according to PE teachers' representations. We propose some important training content in adapted PE for (future) PE teachers.